Endoscopic Corneal Neurotization: Technique and Initial Experience. Issue 1 (January 2018) - Leyngold, Ilya; Weller, Christopher; Leyngold, Mark; Tabor, Mark
Abstract : Purpose: The authors describe a minimally invasive surgical technique to re-establish corneal sensibility in a patient with neurotrophic keratopathy with the supraorbital nerve harvested endoscopically. Methods: Pedicled contralateral supraorbital nerve was harvested endoscopically through small eyelid crease and scalp incisions and transferred to the affected eye. Results: Endoscopic corneal neurotization was successfully performed with restoration of corneal sensibility and corneal epithelial integrity. Conclusions: The use of an endoscope allows for a minimally invasive approach to successful corneal neurotization with the supraorbital nerve. Abstract : The authors describe a minimally invasive endoscopic technique for corneal neurotization with supraorbital nerve resulting in successful restoration of corneal sensibility.